A Room of One's Own: Autistic Imagination as a Stage for Parasocial Interaction and Social Learning. (29th May 2019) - Visuri, Ingela
Abstract : This article examines the role and function of imagination and parasocial(fiction-based) relations among autistic individuals. In interviews, seventeen high functioning, autistic young adults describe how theyfrequently absorb into daydreams, fantasy literature and multiplayeronline roleplaying games. These findings diverge from previous cognitiveresearch which suggests that imagination is limited in autisticindividuals; a conclusion which is also challenged by scholars incritical autism research. It is suggested that these opposed scholarlyviews can be bridged analytically and methodologically by separatinginterpersonal and intrapersonal imagination, of which only the former, social aspect is affected across the whole autism spectrum. Theresults indicate that parasocial relations are used both for pleasure andto cope with adversities, and that imaginary realms serve as optimalautistic spaces for simulating and practicing social interaction. Thearticle moreover provides a comparative discussion on parasocial andsupernatural relations.